The Development of an Application to Search for OTOP Products in Surin Province - Suksam, Jandara; Yuenying, Winit; Keawbuadee, Piya; Maprasom, Waraluck; Sumkhunthod, Rattana; Potisarn, Nawuttagorn; Khamsuriya, Sahathep; Chaisoong, Umaporn (Journal of Local Governance and Innovation, 2024)
The development of an application on the Android operating system aims to provide accurate, secure, and user-friendly access to product information. This research has three primary objectives: 1) To study the current situation, problems, and needs in searching for OTOP products, 2) To develop an application for guiding and searching for OTOP products, and 3) To study user satisfaction with the application for searching OTOP products. The study surveyed OTOP entrepreneurs and general enthusiasts. The quality of the questionnaire tools was verified by experts. The questionnaires were used to study the current situation, problems, and needs, evaluate the application’s performance, and assess user satisfaction with the OTOP product search application in Surin Province. Data analysis was conducted using descriptive statistics to summarize key findings through a software program. The research found that the overall problem and need for application use were at a moderate level (𝑥̅=3.42). There were four main issues: information not meeting user needs (highest average 𝑥̅=3.52), followed by outdated features (𝑥̅=3.43), security (𝑥̅=3.42), and incomplete information (𝑥̅=3.30). In contrast, overall user satisfaction with the application was at a high level (𝑥̅=4.02), with the top three aspects being security measures (𝑥̅=4.12), accurate and clear product information (𝑥̅=4.06), and appropriate application design (𝑥̅=4.04). The developed application created satisfaction and efficiency in use, particularly in terms of security, data accuracy, and user-friendly design.